The Ecological Character of Water-Bioindicator Macroinvertebrates on Various Agricultural Management: Ecology of Water-Bioindicators in Agriculture - kurnianto, Agung sih; Septiadi, Luhur; Hamidah, Wanda; Magvira, Nur Laila; Sholikah, Ummi (Journal of Tropical Life Science, 2024)
In Indonesia, horticulture is a crucial part of agriculture, heavily reliant on agrochemicals. This study in East Java's Jember and Bondowoso regencies compared conventional and organic farming methods, focusing on their effects on aquatic macroinvertebrates as bioindicators. Research included sites practicing conventional horticulture (cabbage, chili) and organic rice farming. Measurements of water current, pH, conductivity, dissolved oxygen, and temperature were taken, along with macroinvertebrate sampling. Significant differences were found in pH, conductivity, and water current, but not in dissolved oxygen and temperature. Organic farming showed higher macroinvertebrate diversity and lower dominance, especially the Baetidae family. While BMWP-ASPT and EPT scores were similar across methods, organic farming rated unpolluted in biotilik scores. Hierarchical cluster analysis, PCA, and CCA revealed factors influencing the ecological impacts of farming practices. The study underscores how different agricultural methods affect macroinvertebrate diversity, highlighting their role as environmental indicators. This reflects the diverse ecological impacts of agricultural management practices.